Supporting Health-Care Workers and Patients in Quarantine Wards: Evidence From a Survey of Frontline Health-Care Workers and Inpatients With COVID-19 in Wuhan, China - Ting Zhou; Ruiyuan Guan; Susan L. Rosenthal; Scott Moerdler; Ziqi Guan; Liqun Sun (Frontiers Media S.A., 2021)
Objective: Frontline health-care workers and patients with COVID-19 have been identified as high-risk groups for psychological problems. Experience of working or staying in quarantine wards generated psychological stressors for health-care workers and patients with COVID-19. The present study aimed to investigate the psychological symptoms of hospitalized patients with COVID-19 and the health-care workers treating them during the outbreak period, examine the effects of psychological stressors on mental health in both populations and perceived coping resources for both sides.Methods: Three hundred and eleven health-care workers working in a COVID-19 designated hospital in Wuhan, China, and 148 hospitalized patients with COVID-19 in the same hospital participated in this cross-sectional survey conducted in February 2020. Psychological symptoms, psychological stressors, and perceived coping resources were reported by both groups.Results: Thirty-three percent of health-care workers and 35.2% of patients with COVID-19 had significant psychological symptoms that were indicative of a high risk for psychological disorders. Pandemic-related psychological stressors contributed to psychological symptoms for both populations. Concern about patients was one aspect of psychological stressors of frontline health-care workers and both groups perceived support from the opposite side as an important external coping resource.Conclusion: The results shed light on the need to provide psychological support to both frontline health-care workers and patients with COVID-19 and suggest enhancing the treatment alliance might be effective to improve mental health for both populations during the crisis.